Epigenetic inactivation of arginine biosynthesis genes in paediatric intracranial ependymoma. (31st January 2018) - Karakoula, Katherine; Syed, Nelofer; Jacques, Thomas; Phipps, Kim; Thompson, Dominic; Darling, John; Warr, Tracy
Abstract: Aberrant cellular metabolism is recognized as a major event in the growth and development of many cancers and the targetting of metabolic defects in tumour cells represents a new therapeutic opportunity. For example, cells that do not express sufficient levels of argininosuccinate synthetase-1 (ASS1) or argininosuccinate lyase (ASL) become auxotrophic for arginine and require exogenous supply. Arginine deprivation using arginine deiminase (ADI-PEG20) is currently under evaluation in clinical trials for adult GBM. In this study, we investigated the arginine biosynthesis pathway in paediatric intracranial ependymoma, comprising 24 fresh frozen biopsies and 17 short-term cell cultures of low passage (<10). The methylation status of ASS1 and ASL was assessed by methylation-specific PCR and gene expression levels were measured using real-time Q-PCR analysis. The response of ependymoma cell cultures in vitro to ADI-PEG20 was determined at various time points using the sulphorodamine B (SRB) assay. Promoter hypermethylation of ASS1 was present in 41.5% ependymoma (17/41 samples) and methylation correlated with down-regulation of ASS1 expression (p<0.0001, Fisher's exact test). Importantly, methylation and expression status was maintained in 6 patient-derived cell cultures for which paired biopsies were available. Conversely, methylation of ASL was not detected in any samples. Treatment with ADI-PEG20 inhibited proliferation of ependymoma cells only in those cultures with methylation-dependent silencing of ASS1. Our findings suggest that argininine depletion therapy may benefit a significant proportion of paediatric patients with intracranial ependymoma.